Pseudomonas aeruginosa Biofilm Removal from Two Kinds of Granite Commonly Found in Catering Kitchen - Khaddouj Amzil; Fatima Hamadi; Hassan Latrache; Rachida Mimouni; Hicham Abou Oualid; Khadija Azelmad; Aissa Saidi; Abdallah Elboulani; Mustapha Mabrouki (International Journal of Microbiology)
The biofilm formation on the surfaces which are in direct contact with food products might lead to their contamination and, consequently, present serious health problems for the consumers. The goals of the present work were to study P. aeruginosa biofilm formation on two granites and to investigate the efficiency of sodium hypochlorite (NaCLO) against the same biofilm formed on these substrata using the plate count method (PCM) and epifluorescence microscopy (EP). More biofilm cells adhered to Rosa Porrino than Gris Pinhel, and the PCM method indicated that NaCLO was efficient against the biofilm installed on the Gris Pinhel at the concentration of 1.5% after 15 min of treatment, while it was not efficient against the one installed on the Rosa Porrino. By contrast, the EP showed that the biofilm persists on two granites after NaCLO treatment, at different concentrations and contact times. In addition, the surface properties of granites such as mineral composition, roughness, and physicochemical properties were determined by X-ray diffraction (XRD), scanning electron microscopy coupled with electron diffraction spectroscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS), Fourier transform infrared (FTIR), atomic force microscopy (AFM), and contact angle measurement (CAM), respectively. The results revealed that Gris Pinhel is hydrophilic with a high roughness value and Rosa Porrino is hydrophobic with low roughness, while both of them contain the quartz, feldspar, and mica as the main dominant compositions.